Employee Training as a Panacea for Career Development: Evidence from South African Police Service - Khayelihle, Ngema; Rajlal, Ashnee; Utete, Reward (Acta Universitatis Danubius. Œconomica, 2022)
Indeed, the significance of career development in contemporary workplace practices is salient as many reports of frustration about poor career growth surge. Although the issue of security and safety of any country is accorded great priority across the world, in the previous millennium organisations in the security and safety industry particularly in South Africa have been reluctant to continuously upgrade the competencies of their employees which results in serious deficit of skills as corporate ladder rises. The crux of this paper is to investigate the degree to which employee training impact career development at South African Police Service. A descriptive research design and quantitative research method used in this research. The sample for this study was 139 employees. Self-structured questionnaire was utilised to gather the data. The multi-linear regression analysis was utilised and key results of the study indicated that the employee training is a catalyst for career development. Understanding of employee training and its implications for career development at the workplace is critical in that it allows organisations to design interventions that prevent the escalation poor growth of employees and manage their consequences when they arise.